2011
DOI: 10.1203/pdr.0b013e318232a984
|View full text |Cite
|
Sign up to set email alerts
|

Farnesol Decreases Biofilms of Staphylococcus epidermidis and Exhibits Synergy With Nafcillin and Vancomycin

Abstract: Biofilm infections are frequently caused by S. epidermidis, are resistant to antimicrobial agents and adversely affect patient outcomes. We evaluated farnesol, the Candida quorum sensing molecule, on S. epidermidis biofilms, in vitro and in vivo. We evaluated ED50, ED75 and ED90 –(drug concentrations causing 50%, 75% and 90% inhibition respectively) of farnesol and evaluated synergy with nafcillin and vancomycin. Farnesol’s effects on morphology of S. epidermidis biofilms were analyzed using confocal microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 24 publications
3
38
1
2
Order By: Relevance
“…Further reading on in vivo models for anti-biofilm drug discovery, and translational research of echinocandins can be found in recent reviews [107,148,149]. [61] in vivo model of catheter biofilm in rabbit C. albicans casp, mica [169,170] in vivo model of subcutaneous device infection in rat C. albicans anid, casp, mica, casp + diclofenac [171][172][173] C. glabrata anid, casp, mica [174] mixed species oral biofilm, in vitro QS (quorum-sensing) interference in biofilm from dental plaque isolates C. albicans, C. glabrata, S. mutans tt-farnesol, tyrosol [79,175] Gram-positive bacteria usnic acid [176] in vivo model of biofilm infection by clinical isolates in Galleria mellonella larvae C. albicans anid [177] in vitro biofilms in catheters and biomaterials, simulated endocardial vegetation (SEV) [183] in vivo model of foreign-body infection in guinea pig C. albicans casp, anid [140] in vivo murine model of cystic fibrosis Burkholderia cepacia, P. aeruginosa patulin [184] synthetic urine medium C. albicans casp [185] Notes: anid: anidulafungin; casp: caspofungin; mica: micafungin; amb: amphotericin B; tt-farnesol: trans,trans-farnesol.…”
Section: Discussionmentioning
confidence: 99%
“…Further reading on in vivo models for anti-biofilm drug discovery, and translational research of echinocandins can be found in recent reviews [107,148,149]. [61] in vivo model of catheter biofilm in rabbit C. albicans casp, mica [169,170] in vivo model of subcutaneous device infection in rat C. albicans anid, casp, mica, casp + diclofenac [171][172][173] C. glabrata anid, casp, mica [174] mixed species oral biofilm, in vitro QS (quorum-sensing) interference in biofilm from dental plaque isolates C. albicans, C. glabrata, S. mutans tt-farnesol, tyrosol [79,175] Gram-positive bacteria usnic acid [176] in vivo model of biofilm infection by clinical isolates in Galleria mellonella larvae C. albicans anid [177] in vitro biofilms in catheters and biomaterials, simulated endocardial vegetation (SEV) [183] in vivo model of foreign-body infection in guinea pig C. albicans casp, anid [140] in vivo murine model of cystic fibrosis Burkholderia cepacia, P. aeruginosa patulin [184] synthetic urine medium C. albicans casp [185] Notes: anid: anidulafungin; casp: caspofungin; mica: micafungin; amb: amphotericin B; tt-farnesol: trans,trans-farnesol.…”
Section: Discussionmentioning
confidence: 99%
“…VAN has a low degree of synergism with the antibacterial nisin against some S aureus strains [13]. Also, VAN has synergism with sulfamethoxazole/trimethoprim and rifampin against some Staphylococcus strains; however, when combined with imipenem and other drugs, VAN has synergistic effects against a broader range of methicillinresistant, coagulase-negative, and biofilm forms of Staphylococcus [30,34]. The synergism between CHX and VAN, like with the other examples mentioned, may ultimately allow for the reduced amount of total drug dosage clinically as well as greater antibiotic efficacy, coverage of multiple strains, and decreased incidence of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…FTR2) and genes encoding heat shock proteins (HSP70, HSP90, HSP104, CaMSI3, and SSA2) (Cao et al, 2005). In Staphylococcus epidermidis, farnesol inhibited in vitro and also in vivo biofilm formation in a mouse model showing also a synergistic effect with nafcillin and vancomycin antibiotic treatments (Pammi, Liang, Hicks, Barrish, & Versalovic, 2011). It was also reported that Pneumocystis spp and Staphylococcus aureus biofilms were inhibited by farnesol treatment (Cushion, Collins, & Linke, 2009;Jabra-Rizk, Meiller, James, & Shirtliff, 2006).…”
Section: Food Phytochemicalsmentioning
confidence: 97%